DINAMIKA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEMBANGUN MOTIVASI KERJA GURU DI SDN 07 SUNGAI BEREMAS - Ahyarti, Arya; Gistituati, Nurhizrah; Anisah, Anisah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the dynamics of transformational leadership implemented by the principal in an effort to build teacher work motivation at SDN 07 Sungai Beremas. Transformational leadership, with a focus on providing inspiration, intellectual stimulation, individual consideration, and idealized influence, is believed to have a significant role in increasing teacher intrinsic and extrinsic motivation. Through a qualitative approach with a case study method, this study explores in depth how the principal implements the principles of transformational leadership in daily interactions with teachers. Data were collected through observation, in-depth interviews with the principal and teacher representatives, and analysis of related documents. The results of the study are expected to provide a comprehensive understanding of effective transformational leadership strategies in fostering teacher work motivation, as well as identifying supporting and inhibiting factors in its implementation in the context of elementary schools. The implications of this study are expected to provide practical contributions to the development of school leadership that is oriented towards improving the quality of human resources, especially teacher work motivation.